KEAGAMAAN MUHAMMADIYAH: DASAR, PRINSIP DAN APLIKASI - Mulyadi, Mulyadi; Afriko, Novik; Mursal, Mursal; Lahmi, Ahmad (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This article discusses the basics, principles, and religious applications of Muhammadiyah as one of the largest Islamic organizations in Indonesia. Muhammadiyah was founded with the vision of realizing a truly Islamic society through a reform approach (tajdid) and practicing the values of the Koran and Sunnah. This study uses a qualitative method with descriptive analysis based on literature studies of official Muhammadiyah documents and related academic references. The results of the study show that Muhammadiyah has succeeded in implementing the principles of monotheism, amar ma'ruf nahi munkar, tajdid, and moderation in various fields, such as education, health, economics, and social. As a progressive Islamic movement, Muhammadiyah not only purifies Islamic teachings but also answers the challenges of globalization and modernity through relevant and inclusive business charities. This article underlines Muhammadiyah's role as a model of an Islamic organization that is responsive to the dynamics of the times, without ignoring universal Islamic values.Keywords: Muhammadiyah, Monotheism, Tajdid, Amar Ma'ruf Nahi Munkar, Islamic Moderation, Progressive Islam